Bacterial Symbionts in Lepidoptera: Their Diversity, Transmission, and Impact on the Host - Paniagua Voirol, Luis R.; Frago, Enric; Kaltenpoth, Martin; Hilker, Monika; Fatouros, Nina E. (Frontiers in Microbiology, 2018)
The insect´s microbiota is well acknowledged as a “hidden” player influencing essential insect traits. The gut microbiome of butterflies and moths (Lepidoptera) has been shown to be highly variable between and within species, resulting in a controversy on the functional relevance of gut microbes in this insect order. Here, we aim to (i) review current knowledge on the composition of gut microbial communities across Lepidoptera, (ii) elucidate the drivers of the variability in the lepidopteran gut microbiome, and provide an overview on (iii) routes of transfer and (iv) the putative functions of microbes in Lepidoptera. To find out whether Lepidopterans possess a core gut microbiome, we compared studies of the microbiome from 30 lepidopteran species. Gut bacteria of the Enterobacteriaceae, Bacillaceae and Pseudomonadaceae families were the most widespread across species, with Pseudomonas, Bacillus, Staphylococcus, Enterobacter and Enterococcus being the most common genera. Several studies indicate that habitat, food plant and age of the host insect can greatly impact the gut microbiome, which contributes to digestion, detoxification, or defense against natural enemies. We mainly focus on the gut microbiome, but we also include some examples of intracellular endosymbionts. These symbionts are present across a broad range of insect taxa, and are known to exert different effects on their host, mostly including nutrition and reproductive manipulation. Only two intracellular bacteria genera (Wolbachia and Spiroplasma) have been reported to colonize reproductive tissues of Lepidoptera, affecting their host’s reproduction. We explore routes of transmission of both gut microbiota and intracellular symbionts, and have found that these microbes may be horizontally transmitted through the host plant, but also vertically via the egg stage. More detailed knowledge about the functions and plasticity of the microbiome in Lepidoptera may provide novel leads for the control of lepidopteran pest species.